PENGARUH SISTEM OLAH TANAH DAN APLIKASI MULSA BAGAS PADA PERTANAMAN TEBU (Saccharum officinarum L.) TERHADAP POPULASI MIKROORGANISME PELARUT FOSFAT DI PT. GMP LAMPUNG TENGAH - Nyang Vania Ayuningtyas Harini; Ainin Niswati; Sri Yusnaini (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2014)
Sugarcane plantation atPT Gunung Madu Plantation (GMP) has done intensive tillage since 1975. To maintain sustainable production and soil fertility is necessary to manage soil according to good soil conservation. The good choice to maintaince soil quality is no-tillage and mulching system. The research was carried out since July 2010,phosphate solubilizing microorganismwere observedat9 and 12 months after ratoon one, in April and July 2012. The research was designed as a split plot with a randomized block design (RBD) with 5 replications . Main plot are tillage system that consists of no-tillage (T0) and tillage (T1). The subplots were application of baggase mulch. Consisting ofwithout bagasse mulch application (M0) andwith 80 t ha-1baggase mulch (M1). Data were analyzed by analysis of variance at the level of 1% and 5%, which previously had been analyzed with the Bartlett test forHomogeneity and Additivity with Tukey test, and followed by LSD test at the level of 1% and 5%. The results showed that the tillage system and bagasse mulch application did not give significant effect on the population of phosphate solubilizing microorganism. Correlation test results showed that the phosphate solubilizing microorganism population has no correlation with organic C, total N, soil pH, soil moisture, soil temperature, and available P.